The regensburg protocol for spinal metastases - Pérez Atanasio,José Manuel (2013)
Metastases to the vertebrae are a common problem in the practice of a spine surgeon. Therapeutic intervention can alleviate pain, preserve or improve neurologic function, achieve mechanical stability, optimize local tumor control, and improve quality of life. Treatment options available for metastatic spine tumors include radiation therapy, chemotherapy and surgery. This article is focused on the decision making for spine surgeons and shows the protocol to treat spinal metastases at the University Hospital of Regensburg, Germany.